Influence of juvenile idiopathic arthritis on the quality of life of young adults in the transition period to adult rheumatologic care - Dzhus, Marta (Psychosomatic Medicine and General Practice, 2017)
Background. Young adults with juvenile idiopathic arthritis (JIA) often have an active disease with significant functional impairment in adulthood that can affect their physical and mental functions. Aim. To determine the impact of JIA on quality of life (QoL) in young adults with JIA during the transition healthcare. Materials and methods. The cross-sectional study of 89 young adults aged 16 to 22 years with a history of JIA regardless of the presence or absence of active inflammation at the time of the survey was performed in the Oleksandrivsky Central Clinical Hospital in Kyiv, Ukraine in the period between April 2015 and February 2017. 25 age- and sex-matched controls (without rheumatic disease) were included. There was performed an evaluation of the age at disease onset, duration, JIA activity, received therapy and quality of life. Results. Out of 89, 37 (41,6%) patients were considered to be in remission. Juvenile idiopathic arthritis had a large impact on the physical scales of quality of life. Patients with JIA had worse (p <0.001) physical health in comparison with the control group. The pain was the most important factor affecting the quality of life in cases of juvenile idiopathic arthritis. The indices responsible for the physical (p<0.001), role (borderline significance, p=0.04) functioning, and intensity of pain (p<0.001) were decreased, compared with the control group. However, the indicators responsible for psychological function in patients with JIA did not differ from the control group. The correlation analysis revealed significant negative association between disability severity (HAQ) and physical function (r=-0,56, p<0.001), role function (r=-0,33, p<0.001), pain intensity (r=-0,60, p<0.001), general health (r=-0,40, p=0.01), vital activity (r=-0,46, p<0.001), social function (r=-0,48, p<0.001), mental health (r=-0,42, p<0.001). Conclusion. In our transitional cohort of patients at the era of biological therapies, juvenile idiopathic arthritis had a larger effect on the physical than mental SF-36 subscale. The pain was the main factor influencing the quality of life.